Risk factors for low birth weight in Rio Grande do Sul State, Brazil: classical and multilevel analysis Fatores de risco para baixo peso ao nascer no Estado do Rio Grande do Sul, Brasil: análise clássica e multinível - Anaelena Bragança de Moraes; Roselaine Ruviaro Zanini; João Riboldi; Elsa Regina Justo Giugliani (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
The objective of this study was to identify risk factors for low birth weight in singleton live born infants in Rio Grande do Sul State, Brazil, in 2003, based on data from the Information System on Live Births. The study used both classical multivariate and multilevel logistic regression. Risk factors were evaluated at two levels: individual (live births) and contextual (micro-regions). At the individual level the two models showed a significant association between low birth weight and prematurity, number of prenatal visits, congenital anomalies, place of delivery, parity, sex, maternal age, maternal occupation, marital status, schooling, and type of delivery. In the multilevel models, the greater the urbanization of the micro-region, the higher the risk of low birth weight, while in less urbanized micro-regions, single mothers had an increased risk of low birth considering all live births. Low birth weight varied according to micro-region and was associated with individual and contextual characteristics. Although most of the variation in low birth weight occurred at the individual level, the multilevel model identified an important risk factor in the contextual level. O objetivo deste estudo foi identificar os fatores de risco para o baixo peso ao nascer de nascidos vivos de gestação simples no Rio Grande do Sul, Brasil, em 2003, obtidos do Sistema de Informações sobre Nascidos Vivos. Foram utilizadas regressão logística múltipla clássica e multinível. Os fatores de risco foram avaliados no nível individual (nascidos vivos) e contextual (microrregiões). No nível individual dos dois modelos foi encontrada associação significativa entre baixo peso ao nascer e prematuridade, consultas pré-natais, anomalia congênita, local do nascimento, paridade, sexo, idade materna, ocupação materna, estado civil, escolaridade e tipo de parto. Nos modelos multiníveis, quanto maior a urbanização da microrregião maior o risco de baixo peso ao nascer, e, em microrregiões menos urbanizadas, mães solteiras têm risco aumentado, para todos os nascidos vivos. O baixo peso ao nascer varia com a microrregião e está associado a características individuais e contextuais. Embora a maior parte da variação no baixo peso ao nascer se encontre no nível individual, o modelo multinível identificou um fator de risco importante no nível contextual.